Professoras e professores transexuais e travestis na escola: diálogos sobre formação docente e a inclusão LGBTQIA+ - Medeiros, Jarles Lopes de (2022)
This research investigated the school paths, as students and later as teachers, of teachers with transsexual/transvestite identities who work/worked in basic education in the state of Ceará. It aimed to identify and analyze pedagogical practices of inclusion of these teachers and how they conceive and act in favor of respect and protection of LGBTQIA+ people at school. It aimed to build a narrative bringing these stories closer to academic and social spaces, assuring the interviewed teachers the right to speak and listen, with the appreciation of their educational trajectories. The subjects were six teachers with transsexual/transvestite identities from the state of Ceará, in addition to a high school student, also with a transsexual identity. The research discussed the categories gender, identity, school, inclusive education, training and teaching practice, having as a horizon the transsexuality/transvestility from the perspective of the subjects' orality, with genealogical principles, in which the past and the present intertwined in the narrative, without a linear order. It started with the hypothesis that teachers (subjects of the study), when invested with their transsexual/transvestite identities, are more prone to inclusive pedagogical practices, open to dealing with LGBTQIA+ themes, but also other topics that surround inclusion, such as people with disabilities, ethnic-racial diversities, class, gender, among others. Such hypotheses were verified during the study. From a transdisciplinary perspective (DOSSE, 2013), the qualitative research has cultural historical studies as its methodological matrix (BURKE, 2005), especially the Foucauldian approach (2011; 2014a; 2014b; 2014c). As a procedure for data collection and analysis, Oral History (AMADO; FERREIRA, 2008; JUCÁ, 2013; 2014) and Discourse Analysis (BRANDÃO, 2012; FOUCAULT, 2014a) were used. The results show that, compared to the school before, today there are advances in the way the school and teachers deal with issues related to LGBTQIA+ people, however, more progress is needed, as the institution still presents itself as a environment hostile to diversity. In addition, it was found that the teachers interviewed present pedagogical practices of inclusion related to the theme. In general terms, this research presents a current discussion about the school and the subjects that work in its spaces, teachers and students, with a critical debate about inclusion.